Burkina Faso : Seventh Review Under the Extended Credit Facility Arrangement-Press Release and Staff Report. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2017)
This paper discusses Burkina Faso's Seventh Review Under the Extended Credit Facility (ECF) Arrangement. Economic growth rose to almost 6 percent in 2016, driven by increases in cotton and gold production, following two years of relatively subdued economic performance related to the political transition. Program performance continues to be satisfactory, with all quantitative performance criteria and structural benchmarks met for the seventh and final review; two indicative targets were missed by small margins. Based on the authorities' program performance and assurances going forward, the IMF staff recommends the completion of the seventh and final review under the ECF arrangement.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet